Outcomes of Laparoscopic Splenectomy Using Hem-O-Lok Clips: Experience from 38 Cases - Nguyen, Huy Toan; Le, Anh Xuan; Pham, Minh Tuan; Tran, Xuan Cong; Nguyen, Van Huong (Tạp chí Y Dược Huế, 2025)
Background: Based on research activities and clinical practice at Nghe An Friendship General Hospital, we conducted this study to evaluate the outcomes of laparoscopic splenectomy using Hem-O-Lok clips at our institution. Introduction: A retrospective, cross-sectional study on 38 patients who underwent laparoscopic splenectomy at the Nghe An General Friendship Hospital from January 2020 to January 2025. Methods: A retrospective, cross-sectional study on 38 patients who underwent laparoscopic splenectomy at the Nghe An General Friendship Hospital from January 2020 to January 2025. Results: There were 38 patients, including 27 males (71%) and 11 females (29%), with an average age of 39.5 ± 10.2 years (range 18 - 65 years). The the main indications for splenectomy included hematologic disorders (34.2%), splenic tumors (34.2%), and splenic cysts (21.1%). The success rate of the surgery was 36 cases (94.7%), with total splenectomy performed in 33 cases (86.8%) and splenectomy with accessory spleen removal in 3 cases (7.9%). Splenic artery control at the splenic hilum was achieved in 12 cases (33.3%). Postoperative complications were observed in 5 cases (13.2%), including wound infection, pancreatic fistula, and splenic vein thrombosis. Good outcomes were achieved in 86.1% of patients, with no poor outcomes recorded. Conclusion: Laparoscopic splenectomy for the treatment of hematopoietic disorders and intrinsic diseases of the spleen is a safe method with a high success rate. The use of Hem-O-Lok instead of staplers for vascular control helps reduce surgical costs while still providing good outcomes for patients.